VARIOUS TECHNIQUES FOR RADICAL TRACHELECTOMY: ONCOLOGIC AND REPRODUCTIVE OUTCOMES - S. A. Skugarev; Е. G. Novikova; A. S. Shevchyuk (Сибирский онкологический журнал, 2018)
The purpose of the study was to review available data on various techniques for radical trachelectomy, inclusion criteria, advantages and disadvantages.Material and methods. A systematic literature search was conducted in the electronic databases of Medline, Russian Science Citation Index, and Russian State Library in the interval time between 1997 and 2017.Results. To date, only radical trachelectomy has shown its value regarding both aspects of oncologic and reproductive outcomes in patients with invasive cervical cancer. There are currently 5 approaches to radical trachelectomy: transvaginal approach with laparoscopic pelvic lymphadenectomy, abdominal, laparoscopic, robot-assisted and laparoscopic – vaginal approach. Each technique has its advantages and disadvantages.Conclusion. Over the last years, radical trachelectomy has been recognized as a valuable fertility-preserving option for women of child-bearing age with invasive cervical cancer. Radical trachelectomy should be performed by highly skilled surgeons in specialized clinics.